Stylistic aspects of English and Polish medical records. Implications for translation - Paulina Pietrzak (JoSTrans: The Journal of Specialised Translation)
The present paper attempts to delineate variations in the style and register of medical documentation in English and Polish based on a range of sample discharge summaries. The aim of such a differentiation is to suggest implications for specialised translation and guidance for translation trainees. The discharge summary is a vital tool used to communicate a framework of healthcare between hospitals, doctors and patients- often internationally, thus the purpose of its translation is to communicate this globally in the most effective manner. This article demonstrates syntactic differences in sentence patterns in medical documentation of both languages and discusses their degree of formality reflected i.a. in the level of (in)directness and (im)personality. It also observes the inclusion (or lack thereof) of certain information in the analysed material. Numerous discrepancies in linguistic, stylistic and composition features indicate that it is necessary for the translator to implement certain stylistic alterations. The author presents a number of tips offering a functional approach to translating such texts.